2022
DOI: 10.1021/acs.chemrev.1c00991
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazole and Its Analogues: New Surrogates for Diazo Compounds

Abstract: Readily accessible and shelf-stable 1,2,3-triazole and its analogues such as pyridotriazole, triazoloindole, benzotriazole, and thiadiazole exist in equilibrium with their ring-opened isomers, viz., diazo compounds. These ring-opened isomers could be trapped by various metal catalysts (e.g., Rh, Pd, Cu, Co, Ag, etc.) to generate the corresponding metal carbenoids with extrusion of nitrogen. As a consequence, these unique N-heterocycles facilitate access to a realm of N-containing complex structural motifs of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(41 citation statements)
references
References 397 publications
0
41
0
Order By: Relevance
“…Anbarasan's group reported the synthesis of benzopyran compounds from in situ generated α-imino rhodium carbenes and o -QM intermediates via the rhodium-catalyzed denitrogenative transannulation of N -sulfonyl-1,2,3-triazoles with ortho -hydroxy benzhydryl alcohols. 35 N -Sulfonyl-1,2,3-triazole derivatives 122 are the precursors of α-diazoimines 36 via ring–chain isomerism, in the presence of a rhodium catalyst (Rh 2 (Oct) 4 ), to form α-imino rhodium carbenes 125 (Scheme 21a). The nucleophilic attack of the carbonyl group of o -QM 126 onto the electrophilic α-imino rhodium carbene 125 then generates the carbonyl ylide 127 (Scheme 21a).…”
Section: Reactivity Of Qms With α-Diazocarbonyl Compounds and Their P...mentioning
confidence: 99%
“…Anbarasan's group reported the synthesis of benzopyran compounds from in situ generated α-imino rhodium carbenes and o -QM intermediates via the rhodium-catalyzed denitrogenative transannulation of N -sulfonyl-1,2,3-triazoles with ortho -hydroxy benzhydryl alcohols. 35 N -Sulfonyl-1,2,3-triazole derivatives 122 are the precursors of α-diazoimines 36 via ring–chain isomerism, in the presence of a rhodium catalyst (Rh 2 (Oct) 4 ), to form α-imino rhodium carbenes 125 (Scheme 21a). The nucleophilic attack of the carbonyl group of o -QM 126 onto the electrophilic α-imino rhodium carbene 125 then generates the carbonyl ylide 127 (Scheme 21a).…”
Section: Reactivity Of Qms With α-Diazocarbonyl Compounds and Their P...mentioning
confidence: 99%
“…Further developments of metalloradical chemistry toward heterocycle synthesis has been extensively reported and updated. 8c 5 32…”
Section: Radical Heterocyclizationmentioning
confidence: 99%
“…Further developments of metalloradical chemistry toward heterocycle synthesis has been extensively reported and updated. 8c, 5,32 Scheme 11 Visible-light-induced palladium-catalyzed generation of aryl radicals from aryl triflates toward oxindoles and isoindolin-1-ones…”
Section: Light-free Radical Heterocyclizationmentioning
confidence: 99%
“…1,2,3-Benzotriazoles are an important class of heterocycles that have found widespread applications in organic synthesis, medicinal chemistry, and material science [ 9 , 10 , 11 , 12 , 13 ]. Historically, it has been reported that some 1-substituted 1,2,3-benzotriazoles could undergo denitrogenative transformations to generate other valuable products.…”
Section: Introductionmentioning
confidence: 99%